PENGARUH VARIETAS KEDELAI TERHADAP MUTU TAHU YANG DIHASILKAN - Budi Santosa; Gatut Suliana (Universitas Tribhuwana Tunggadewi, 2009)
This Research aim to look for best soy variety for the making of tofu. This research is executed in Laboratory Engineering Process and System Produce University of Tribhuwana Tunggadewi Malang. Device attempt which is used in this research is Random Device Complete with one factor, as its factor soy variety which consist of three level that is Wilis variety, Kaba variety and Import variety, each level repeated the five of times. All soy variety wear in this research is obtained from BALITKABI Malang. Result of research indicate that tofu having best quality is made of tofu is soy of variety Kaba with protein content 14,63%, water content 77,22% and also result of from test of organoleptik by using 20 panelist people tell to be taken a fancy to or can be accepted